2019
DOI: 10.1371/journal.pone.0219408
|View full text |Cite
|
Sign up to set email alerts
|

Infrastructure expansion challenges sustainable development in Papua New Guinea

Abstract: The island of New Guinea hosts the third largest expanse of tropical rainforest on the planet. Papua New Guinea—comprising the eastern half of the island—plans to nearly double its national road network (from 8,700 to 15,000 km) over the next three years, to spur economic growth. We assessed these plans using fine-scale biophysical and environmental data. We identified numerous environmental and socioeconomic risks associated with these projects, including the dissection of 54 critical biodiversity habitats an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 38 publications
3
27
0
Order By: Relevance
“…28 (4): 1517-1529 Vegetation or healthy plants in an area were affected by LST variation (Rahmad et al, 2019). Two studies reported on the increasing rate of forest conversion in the areas of Papua New Guinea and Papua (Alamgir et al, 2019;Austin et al, 2019). This deforestation is suspected to be the cause of an increase in temperatures in the area.…”
Section: Resultsmentioning
confidence: 99%
“…28 (4): 1517-1529 Vegetation or healthy plants in an area were affected by LST variation (Rahmad et al, 2019). Two studies reported on the increasing rate of forest conversion in the areas of Papua New Guinea and Papua (Alamgir et al, 2019;Austin et al, 2019). This deforestation is suspected to be the cause of an increase in temperatures in the area.…”
Section: Resultsmentioning
confidence: 99%
“…We obtained spatial data on planned and ongoing road and dam construction projects in Sarawak from a variety of regional and national sources in an endeavour to include the majority of the projects in our analyses. We digitized the Pan-Borneo Highway, Sarawak (Fig 1) from the project's map [11,32] following the procedures listed in Alamgir et al [21,23] and Sloan et al [26]. The project map was prepared using fine scale biophysical data for the project design and implementation [11,32].…”
Section: Roads and Hydroelectric Damsmentioning
confidence: 99%
“…Connectivity is important for wildlife communities to shift from one suitable habitat to another across the landscape. We assessed the impacts of the highway and hydroelectric dams on landscape connectivity in Sarawak conducting a morphological spatial pattern analysis (MSPA) using Graphical User Interface for the Description of Image Objects and their Shapes (Guidos Toolbox 2.6 version 4) [36, 37], following Alamgir et al [21,23] and Sloan et al [22]. The MSPA analysis delineated forest areas in Sarawak into distinct forest-landscape elements including core forest (forest � 500 m from the nearest forest edge), connectivity forest (forest corridors that connect different core forest patches or different segments of a core-forest patch) and edge forest (forest < 500 m from an edge).…”
Section: Landscape Connectivitymentioning
confidence: 99%
See 2 more Smart Citations